2021
DOI: 10.1177/09557490211058869
|View full text |Cite
|
Sign up to set email alerts
|

Library Websites During the COVID-19 Pandemic

Abstract: The outbreak of the COVID-19 pandemic has been shown to impact the business environment in different ways. The current paper presents how the university and research library websites in Tanzania responded to the changes in the working environment and style following the outbreak of COVID-19. This study employed a content analysis method to collect and analyse data from academic and research library websites in Tanzania. This study focuses on how library websites in Tanzania were used to update and connect libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Rafiq et al (2021) stated that significant barriers such as lack of budget, digital divide, low computer literacy skills, slow internet, inadequate online resources and web portal/library website impede libraries and LIS professionals in their shift from physical to digital mode. Mnzava and Katabalwa's (2021) study found that libraries in Tanzania used library websites that help LIS professionals to share updates and connect their library users with appropriate information resources and services during the pandemic. Furthermore, to maintain social distance in the workplace, library staff and users/patrons should be aware of the health protocols, for example, what they should do if they ill or unwell.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Rafiq et al (2021) stated that significant barriers such as lack of budget, digital divide, low computer literacy skills, slow internet, inadequate online resources and web portal/library website impede libraries and LIS professionals in their shift from physical to digital mode. Mnzava and Katabalwa's (2021) study found that libraries in Tanzania used library websites that help LIS professionals to share updates and connect their library users with appropriate information resources and services during the pandemic. Furthermore, to maintain social distance in the workplace, library staff and users/patrons should be aware of the health protocols, for example, what they should do if they ill or unwell.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%